Influencia del presupuesto en las estrategias de redes sociales y la ventaja competitiva de las franquicias de alimentos - Marcondes Coelho, Amanda (2022)
The study aimed to analyze the influence of budget on social media strategies and on the competitive advantage of food franchises. For that, a survey was applied with 84 food franchise managers and the quantitative analysis was performed using structural equation modeling. The results indicated that the planning budget positively influences the competitive advantage, which is related to the performance of companies. It was also observed that the relationship between the budget for dialogue and the competitive advantage in the market is mediated by the social media strategy. The results also highlight that the greater the use of budget for communication and motivation functions, the greater the implementation of social media strategies. The findings add to the corporate budget literature, suggesting that it can foster greater performance in relation to competitors. Evidence also suggests that social media strategies are used to reinforce the effects of management controls on organizational results.